MicroRNA-210 Enhances Fibrous Cap Stability in Advanced Atherosclerotic Lesions. Issue 4 (17th February 2017) - Eken, Suzanne M.; Jin, Hong; Chernogubova, Ekaterina; Li, Yuhuang; Simon, Nancy; Sun, Changyan; Korzunowicz, Greg; Busch, Albert; Bäcklund, Alexandra; Österholm, Cecilia; Razuvaev, Anton; Renné, Thomas; et al.
Abstract : Rationale: : In the search for markers and modulators of vascular disease, microRNAs (miRNAs) have emerged as potent therapeutic targets. Objective: : To investigate miRNAs of clinical interest in patients with unstable carotid stenosis at risk of stroke. Methods and Results: : Using patient material from the BiKE (Biobank of Karolinska Endarterectomies), we profiled miRNA expression in patients with stable versus unstable carotid plaque. A polymerase chain reaction–based miRNA array of plasma, sampled at the carotid lesion site, identified 8 deregulated miRNAs (miR-15b, miR-29c, miR-30c/d, miR-150, miR-191, miR-210, and miR-500). miR-210 was the most significantly downregulated miRNA in local plasma material. Laser capture microdissection and in situ hybridization revealed a distinct localization of miR-210 in fibrous caps. We confirmed that miR-210 directly targets the tumor suppressor gene APC (adenomatous polyposis coli), thereby affecting Wnt (Wingless-related integration site) signaling and regulating smooth muscle cell survival, as well as differentiation in advanced atherosclerotic lesions. Substantial changes in arterial miR-210 were detectable in 2 rodent models of vascular remodeling and plaque rupture. Modulating miR-210 in vitro and in vivo improved fibrous cap stability with implications for vascular disease. Conclusions: : An unstable carotid plaque at risk of stroke is characterized by low expression of miR-210. miR-210 contributes to stabilizing carotid plaques through inhibition of APC, ensuring smooth muscle cell survival. We present local delivery of miR-210 as a therapeutic approach for prevention of atherothrombotic vascular events. Abstract : Supplemental Digital Content is available in the text.